2020
DOI: 10.1177/2378023120916125
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing Moral Cognition: Culture in Action, Situations, and Relationships

Abstract: Dual-process theories of morality are approaches to moral cognition that stress the varying significance of emotion and deliberation in shaping judgments of action. Sociological research that builds on these ideas considers how cross-cultural variation alters judgments, with important consequences for what is and is not considered moral behavior. Yet lacking from these approaches is the notion that, depending on the situation and relationship, the same behavior by the same person can be considered more or less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 136 publications
2
36
0
Order By: Relevance
“…Climate change decision-makers at all scales will increasingly make decisions in and about new and uncertain situations. Sociological studies have shown that alongside moral identity (Stets and Carter, 2012;Shadnam, 2020), social relationships and changes in situations shape moral judgements and behaviour (Luft, 2020). When faced with unfamiliar situations, people do not revert to the unconscious moral intuitions used in normal day-to-day situations.…”
Section: Morals As Relational Situated and Dynamicmentioning
confidence: 99%
“…Climate change decision-makers at all scales will increasingly make decisions in and about new and uncertain situations. Sociological studies have shown that alongside moral identity (Stets and Carter, 2012;Shadnam, 2020), social relationships and changes in situations shape moral judgements and behaviour (Luft, 2020). When faced with unfamiliar situations, people do not revert to the unconscious moral intuitions used in normal day-to-day situations.…”
Section: Morals As Relational Situated and Dynamicmentioning
confidence: 99%
“…The theoretical utility of analysing tests is rooted in the sociology of critical capacity that asserts that the human capacity to agree, dispute, or criticise is central to social relationships (Boltanski & Thévenot, 1999). Difficult questions about morality and moral judgements in challenging times, and how they affect actions and relationships, have been central to the COVID-19 crisis (Luft, 2020). By wrapping this analysis around the moment of a test, as well as paying attention to critical moments whereby value frameworks are questioned, this paper aims to be theoretically generative for contributing to ongoing research on the institutional work around elite transnational education's maintenance and disruption (Dansou & Langley, 2012).…”
Section: Tests Critical Capacities and Changing Regimes Of Student Mobilitymentioning
confidence: 99%
“…In response to this article's research question regarding building a model of economic action that incorporates both moral and self-interested decision-making, I turn to work in neuroscience that grounds dual-process models in empirical work on neural processes. This is crucial because as with behavioral economics, dual-process models in neuroscience have been largely overlooked in sociology (Luft 2020;Vila-Henninger 2015, 2020b, 2021b.…”
Section: Dual-process Model Of Outcomes From Neurosciencementioning
confidence: 99%